Clinical and pathological results of denosumab treatment for giant cell tumors of bone: Prospective study of 14 cases - Mehmet Ali Deveci; Semra Paydaş; Gülfiliz Gönlüşen; Cenk Özkan; Ömer Sunkar Biçer; Mustafa Tekin (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: Giant cell tumor of bone (GCT) is a primary, osteolytic, benign tumor of the bone. Surgery is the commonly used treatment; however, recurrence remains a problem. Receptor activator of nuclear factor kappa B (RANKL) is responsible for the formation of osteoclastic cells. Discovery of RANKL and its human monoclonal antibody, denosumab, led to use of denosumab for treatment of GCT. The aim of this study was to evaluate clinical and pathological results of treatment of GCT with denosumab and to assess adverse effect profile and recurrence rate. Methods: Thirteen patients with 14 lesions were enrolled in the study. Mean age was 38.3 years. Patients were given subcutaneous injections of denosumab (120 mg) every 4 weeks (with additional doses on days 0, 8 and 15 in cycle 1 only) and were radiologically evaluated for tumor response. Pain and functional status were measured using Visual Analog Score (VAS) and Musculoskeletal Tumor Society Score (MSTS). Adverse effects were analyzed after each cycle. Results: Participants were 5 men and 8 women. Mean follow-up was 17 months. One lesion was Campanacci grade I, 8 were grade II, and 5 were grade III. Eight lesions were recurrent, and remaining were primary lesions. After average of 9 cycles (range: 4–17 cycles), all tumors underwent radiological regression. Ten lesions were removed surgically. More than 90% of giant cells were found to have regressed in all pathological specimens. On last follow-up, average VAS was 1 and MSTS was 87%. Fatigue and joint and muscle pain after injections was reported by 46% of patients, and mild hypocalcaemia was seen in 1 patient. Conclusion: Denosumab has been shown to be a successful drug in treatment of GCT. Denosumab can be used as neoadjuvant for all recurrent lesions, grade II lesions with high surgical risk, grade III lesions, and metastatic cases of GCT. Level of evidence: Level IV, Therapeutic study Keywords: Denosumab, Recurrence, Giant cell tumor